2020
DOI: 10.1158/1055-9965.epi-20-0346
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Impairment in Patients with Breast Cancer before Surgery: Results from a CANTO Cohort Subgroup

Abstract: Background: Twenty to 30% of patients with breast cancer have cognitive impairment after surgery and before adjuvant treatment, but very few studies have focused on cognition before any treatment. This study used a subgroup of women with newly diagnosed breast cancer from the French cancer and toxicities (CANTO) cohort to describe cognition before any treatment in comparison with a group of healthy controls (HC).Methods: Cognitive assessment was performed before any breast cancer treatment (surgery or neoadjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
1
22
2
Order By: Relevance
“…The prevalence of cognitive impairment in the present study, detected with MoCA and with a neuropsychological test battery, was much lower than in previous studies performed in patients with other cancers [ 10 , 11 , 12 , 13 , 14 , 48 ]. Prostate cancer, which is an indolent and localized disease in many men, may not induce the same pattern of systemic pathophysiologic alterations as other cancers, which might be a cause of cognitive impairment.…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of cognitive impairment in the present study, detected with MoCA and with a neuropsychological test battery, was much lower than in previous studies performed in patients with other cancers [ 10 , 11 , 12 , 13 , 14 , 48 ]. Prostate cancer, which is an indolent and localized disease in many men, may not induce the same pattern of systemic pathophysiologic alterations as other cancers, which might be a cause of cognitive impairment.…”
Section: Discussioncontrasting
confidence: 87%
“…In some studies, younger participants had more cognitive complaints than older patients, perhaps due to the fact that older patients did not associate their cognitive complaints with cancer treatment, but rather with normal aging [ 5 , 20 , 28 ]. Moreover, younger patients are often well informed, thanks to new information media such as the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies on cognitive effects of specific cancer types or systemic cancer treatments have shown that cancer patients have more often impaired cognitive function than cancer-free controls, sometimes also before start of cancer treatment. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These studies were often limited to specific cancer types. Animal studies have confirmed findings from clinical studies, showing that, for example, both treatment-naïve rodents with cancer and rodents treated with chemotherapy can have cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%